2002
DOI: 10.1017/s0272263102001043
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation and Oral Acquisition of L2 Vocabulary

Abstract: This experimental study investigates the differential effects of three conditions (nonnegotiated premodified input, negotiation without “pushed output” [Swain, 1985], and negotiation plus pushed output) on L2 learners' vocabulary comprehension and acquisition (receptive and productive). Analyses of variance performed on the data indicated that: (a) negotiated interaction had a positive effect on the comprehension of L2 words; (b) only negotiated interaction that incorporated pushed output appeared to have prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(49 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…Within the task treatments, we made a distinction between the presence and absence of interaction (+/-interaction) between the participant and a conversational partner. This has been commonly manipulated in task-based research (e.g., de la Fuente, 2002;Ellis & He, 1999). Thus, each of the four treatments under investigation was different from the previous one in a single aspect.…”
Section: Treatmentmentioning
confidence: 99%
“…Within the task treatments, we made a distinction between the presence and absence of interaction (+/-interaction) between the participant and a conversational partner. This has been commonly manipulated in task-based research (e.g., de la Fuente, 2002;Ellis & He, 1999). Thus, each of the four treatments under investigation was different from the previous one in a single aspect.…”
Section: Treatmentmentioning
confidence: 99%
“…Researchers have generally agreed with the usefulness of circumlocution (see, inter alia, Willems, 1987;Ellis et alii, 1994;De la Fuente, 2002;and Salazar, 2006). We have suggested, following Berry Dörnyei andThurrell (1991), Bravo (1994), and Salazar (2006), among others, that even at lower levels of language learning, it is a useful strategy for students to develop.…”
Section: Resultsmentioning
confidence: 97%
“…Another study that documents whether or not negotiation is necessary for vocabulary acquisition at earlier stages, is that of De la Fuente (2002). In a study of thirty-two intermediate L1 English L2 Spanish students, she showed that circumlocution (which she considers to be interaction), within a negotiated exchange by a NS or NNS, can be highly effective when a word is not known.…”
Section: Circumlocution As Negotiationmentioning
confidence: 99%
“…As another supporting theory for L2 exclusivity, many researchers have insisted that the output hypothesis complements the input hypothesis and is therefore beneficial for generating fluent L2 (Ellis & He, 1999;de la Fuente, 2002). Swain (1995, 128) even extended this, by claiming that there are three strands that are a function of output: 'consciousness-raising', 'hypothesis-testing', and 'meta-linguistic function'.…”
Section: Output Hypothesismentioning
confidence: 99%